The disclosure of sustainable practices in agribusiness companies listed on B3 (Research, Society and Development, 2022)
Sustainability in agribusiness is on the agenda, due to the impacts of its production process on nature and the community, making investors and consumers increasingly demand more transparency on socio-environmental issues, in addition to economic information. In view of this, the study aimed to identify the sustainable actions disclosed in agribusiness companies listed on B3 and relate them to the SDGs. To this end, a descriptive, documental, and qualitative research was developed, using a sample of three companies, whose data were collected through materials on sustainability, published on corporate websites. Based on the content analysis, it was found that SLC Agrícola and BrasilAgro highlight their practices in very detailed annual reports, unlike Terra Santa, which discloses them on its own website in a more summarized manner. Furthermore, it could be inferred that among the cited actions, most are related to SDG 15 - Life on Earth and SDG 8 - Decent Work and Economic Growth. The results found indicate that all the companies surveyed disclose their socio-environmental responsibility, with variations only in the way they present and describe the information.